Malignant granular cell tumor of the breast; literature review - Nalini Gupta; Naveen Sanchety; Pragya Saran Verma; Geeta Verma (Wolters Kluwer Medknow Publications, 2015)
Malignant granular cell tumor (MGCT) is rare tumors that comprise 1-2% of all granular cell tumors. They commonly arise on lower extremity, nuchal region, chest wall, gastrointestinal tract, head, and neck but very rarely in breast. We report a case of a MGCT of breast with review of literature. The patient had noticed a breast mass 4 years back which was operated, and wide local excision was done. The tumor was diagnosed as MGCT. The tumor fulfilled 3 of the 6 criteria of Fanburg-Smith et al. The patient received 8 cycles of chemotherapy thereafter with 4 cycles of antharacycline and 4 of taxanes. However, the tumor reoccurred 4 years after resection and grew rapidly. Contrast-enhanced computed tomography done showed a large lobulated breast mass with axillary lymph node metastasis. She underwent Modified Radical Mastectomy with axillary clearance. The histopathology this time also revealed similar malignant tumor. To the best of our knowledge, only 7 cases have been reported in indexed English literature occurring primarily in breast.